Independent auditors as fiscal gatekeepers - Luigi Alberto Franzoni (Fondazione Eni Enrico Mattei (FEEM), 1997)
This paper develops a framework for the analysis of gatekeeping in tax enforcement, whereby independent auditors are assigned the duty of certifying taxpayers' reports. The equilibrium of the market for gatekeepers' services is characterised, as well as taxpayers' and auditors' optimal behaviour. The paper discusses the optimal structure of the gatekeeping regime and determines the conditions under which it is socially preferable to direct public enforcement.
Keywords: K42; H26; 330; Law enforcement; Tax evasion; Auditing; Collateral liability; Certification; Steuerfahndung; Steuerstrafrecht; Rechnungshof; Theorie